Aerobic and anaerobic performance, ability to repeat sprints, and fatigue development during a basketball game-based drill: correlational study - Hulka, K.; Strniste, M.; Hruby, M.; Bernatik, D.; Belka, J. (International Journal of Performance Analysis in Sport, 2025)
Fatigue development during basketball matches affects player performance. This study aimed to evaluate the relationship among fatigue development during game-based drills, aerobic and anaerobic performance, and repeated sprint ability (RSA) basketball players. The study included 49 male elite basketball players (23.4 ± 3.8 years, body mass 83.0 ± 8.5 kg, height 189.7 ± 8.9 cm). They performed the Yo-Yo Intermittent Test (YIRT2), RSA test, anaerobic performance assessment (300y; "300-yard shuffle running test"), and a game-based drill. The regression equation for total distance decline during last 3 min of each quarter was TD3 min = -38.11 + 0.253·YIRT2 + 0.276·300y + 0.670·RSA with standard erorr =±4.66 for TD3 min during basketball game-based drill. We found out that RSA performance was the most valuable predictor of TD3 min, explaining 44.89% of variance, 300y explained 10.24%, and YIRT2 7.84%. Notably, 37.03% was unexplained by observed variables. Collectively, RSA is considered an important component of basketball in predicting the delay of neuromuscular fatigue during match but not VO2peak.